Split hand and minipolymyoclonus in spinocerebellar ataxia type 3: a case report - Anli Eki; Atsuhiko Sugiyama; Kazumoto Shibuya; Yuki Nakagawa; Takayuki Ishige; Tomoki Suichi; Ryo Otani; Satoshi Kuwabara (BMC Neurology, 2024)
Abstract Background Spinocerebellar ataxia type 3 (SCA3), also known as Machado–Joseph disease, is an autosomal dominant neurodegenerative disorder caused by CAG repeat expansion in exon 10 of ATXN3. Extra-cerebellar manifestations, including external ophthalmoplegia, dystonia, Parkinsonism, and peripheral neuropathy, are predominantly present in SCA3 cases. Here, we report a case of SCA3 presenting with a split hand and minipolymyoclonus. Case presentation A 73-year-old female patient presented with a 5-year history of ataxic gait. Neurological examination revealed cerebellar ataxia and minipolymyoclonus in the digits on both sides and muscle atrophy in the right hand, consistent with the split hand pattern. Electrodiagnostic studies demonstrated decreased amplitude of compound muscle action potentials and neurogenic motor unit potentials, indicating lower motor neuron involvement. Conclusions Our patient’s case indicated a split hand and minipolymyoclonus in SCA3. Clinicians should consider these extra-cerebellar manifestations in patients with SCA3. Although neither split hand nor minipolymyoclonus are likely to directly result in a specific etiological diagnosis, a common pathophysiological mechanism for both may be lower motor neuron involvement. This extracerebellar manifestation contributes to narrowing down the diagnostic possibilities for cases presenting with progressive cerebellar ataxia.